Cultural Adaptation in Islamic Education: Navigating Between Tradition and Modernity - Ahmad Wahyudi; Alif Qurrotin Nuriana; Ratna Himawati (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
Cultural adaptation in Islamic education is a challenge and opportunity in facing the dynamics of the times. Islamic education must be able to maintain traditional values ​​while adapting to the challenges of modernity in order to remain relevant. This article discusses how Islamic education can adapt to social, cultural and technological changes without losing its identity. By using qualitative methods based on literature studies, this study explores the strategies and approaches used in the process of cultural adaptation in Islamic education. The results of the study show that the approach of curriculum integration moderation and the use of technology are key factors in aligning tradition and modernity in Islamic education.